Relationship Among Financial Literacy, Attitude and Behaviour - Chaulagain, Ramesh (Social Inquiry: Journal of Social Science Research, 2021)
This study measures relationship among financial literacy, attitude and behaviour. Financial literacy has two attributes, i.e. financial knowledge and skill. Financial attitude is a way of thinking, belief and perception of individuals on personal finance. Financial behaviour is an act of using financial resources for financial independence and well-being. Therefore, measuring the relationship among financial literacy, attitude and behaviour is an important research priority. The study explores the relationship and some factors that contribute to financial behaviours. Using the framework of the theory of planned behaviour, this study interprets its findings. The theory asserts that human behaviours are affected by knowledge and attitude. In this study, a survey was conducted among 393 small borrowers to collect data on financial literacy, attitude and behaviours from four districts of Nepal. Kruskal-Wallis and Chi-Square tests were used to measure the relationships among the variables. The study finds that financial literacy and attitude have significant relationships with the financial behaviours of small borrowers. However, several other factors also affect the behaviours. The study concludes that proper financial education is necessary to change financial literacy and attitude to contribute to small borrowers' financial behaviours. Similarly, the study implies that the government, central bank, and financial service providers are responsible for providing proper and basic financial education to improve financial literacy and thereby change financial behaviours.